2003
DOI: 10.1093/sleep/26.7.871
|View full text |Cite
|
Sign up to set email alerts
|

The Ability to Self-Monitor Performance During a Week of Simulated Night Shifts

Abstract: Overall, results indicate that individuals have only a moderate ability to predict performance impairment during a week of night shifts. It is likely that performance ratings are based, at least to a certain extent, on subjective alertness levels. Furthermore, it seems that rating accuracy is improved on tasks providing performance feedback, such as the PVT. Finally, it appears that after testing, individuals have a more accurate perception of their performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 23 publications
3
51
0
Order By: Relevance
“…A possible reason for this result is that the alertness scales used (SamnPerelli and Visual Analogue Scales) may not have been sensitive enough to detect changes in alertness caused by the prior break length. However, recent publications have reported subjective estimates to have moderate to strong correlations with objective performance, especially at the end of a testing period 28,29) , refuting this argument. The reported lack of significance may instead be caused by limited testing opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason for this result is that the alertness scales used (SamnPerelli and Visual Analogue Scales) may not have been sensitive enough to detect changes in alertness caused by the prior break length. However, recent publications have reported subjective estimates to have moderate to strong correlations with objective performance, especially at the end of a testing period 28,29) , refuting this argument. The reported lack of significance may instead be caused by limited testing opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that for situations involving a single period of acute sleep deprivation using laboratory tasks individuals have an accurate perception of their performance 26,27) . However, during simulated night shift work, the ability to predict performance was moderate at best 28) . In a simulated driving experiment, Horne and Reyner 29) found that while individuals may not be able to predict when they are about to fall asleep or report that they have fallen asleep, they consistently report the awareness of fighting sleep before they are objectively judged to have fallen asleep.…”
Section: Mens Reamentioning
confidence: 94%
“…Thus a person who has 2 h of sleep in the prior 24 would not be covered by the law, and neither would the driver who causes serious injury but not death. Furthermore it overlooks the difficulty that individuals have when measuring their objective performance when fatigued [26][27][28][29] giving rise to potential complaints that people would not have a fair opportunity to comply with a law drafted in this manner (See 41) for a discussion of the application of the fair opportunity principle to involuntariness).…”
Section: A Way Forward?mentioning
confidence: 99%
“…Day sleep in shift workers is often measured as 1-3 h shorter than night sleep on days off, or on day and evening work schedules [10,11]. Following night shifts, most workers report no difficulties falling asleep and latencies to sleep onset are short.…”
Section: Circadian Rhythm Disorders Are Precipitated By Intrinsic Andmentioning
confidence: 99%
“…Despite years of night work, only a minority of workers show an appropriate reorientation of physiological rhythms such as those of 6-sulphatoxymelatonin, plasma melatonin, cortisol, and TSH. This can be related to the observable troughs in vigilance and the fragility of sleep particular to night work [10,11].…”
Section: Circadian Rhythm Disorders Are Precipitated By Intrinsic Andmentioning
confidence: 99%